Samsarah Practices on Affiliates in the Shopee Marketplace: Islamic Economic Law Perspective - Bahri, Syamsul; Busrah, Busrah; Izzah, Ibnu; Muis, Musrini; Halilullah, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study aims to analyze affiliate marketing practices on the Shopee platform from an Islamic economic law perspective, particularly regarding the samsarah (intermediary) contract and percentage-based commissions. This research uses a normative legal methodology from an Islamic economic perspective, presented descriptively. Islamic economic legal theory is used as an analytical instrument to examine the practice of samsarah affiliate marketing in the e-commerce platform Shopee. The results of the study show that from an Islamic legal perspective, affiliate marketing practices on Shopee can be categorized as a valid samsarah contract, by fulfilling two main requirements: clarity of the contract and clarity of the commission. Clarity of the contract relates to the transparency of the type of transaction and the compensation received by the affiliated party. In this case, a percentage-based commission system is acceptable as long as there is no uncertainty (gharar) that would be detrimental to any party. Although some scholars permit percentage-based commissions with an uncertain nominal value, the majority of scholars emphasize the importance of clarity on the commission value that must be agreed upon beforehand so that the transaction remains valid under Islamic economy law. This mechanism aligns with the concept of ittihadul majlis, where agreements and explanations of commissions between merchants and affiliate marketers take place within a clear timeframe, both through platforms and digital communication channels, thus ensuring that the agreement is in line with Islamic economic principles.